Elements Affecting the Development of Effectiveness Direct Selling Network Business in Thailand - Harinpolsith, Chokchai (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The goal of this study was to learn more about: (1) The elements of transformational leadership, corporate culture, corporate climate, and organizational commitment that influence the growth of direct selling network enterprises in Thailand. (2) The importance of increasing the effectiveness of network direct selling firms in Thailand. (3) Directions for executives to improve Thailand's direct selling network enterprises' effectiveness. Twenty executives with businesses in the direct sales network were among the primary informants used in the qualitative investigation. The executives work for direct selling network organizations in Thailand at the team level and higher. Purposive sample of 380 persons from the industry was used in the quantitative research to gather data from direct sales network businesses and employees (team members) that work for companies that run direct sales networks in Thailand. The research's findings revealed that (1) Corporate culture, corporate climate, and dedication to the organization are all changing. The aforementioned elements have an impact on the growth and effectiveness of direct selling network firms in Thailand. The results of the direct influence values were 0.63, 0.50, 0.59, and 1.00. (2) The importance of finance (Lamda = 0.48) ; Customer: (Lamda = 0.64) ; Internal Process (Lamda = 0.53); learning and growth (Lamda = 0.61); and increasing the effectiveness of direct selling network firms in Thailand. (3) Improving product information is a key component of executive guidelines for increasing the effectiveness of Thailand's direct selling network company. Customers that utilize the product directly as well as users of the network itself are all included. To assist improve management efficiency in the field of direct selling firms in Thailand, improving product information should also involve the use of digital technology and social media. Article history : Received 10 October 2021 Revised 1 February 2022 Accepted 4 February 2022 SIMILARITY INDEX = 2.51 %